Acesso à informação governamental: estudo exploratório do papel do Siafi na publicidade da execução do Orçamento Geral da União - Ana Paola de Morais Amorim Valente (2002)
This work has estudied the connection beteween access to governamental information and democracy, analysing the perception that the user of federal governments Siafi (in portugese means Integrated System of Financial Administration) have of Federal Budgets transparency based into information available by this system. This analysis allowed to identify the relationship between the transparency and the possibility of control of parliamentarian above budget execution. The discussion of need of access to governamental information was made based on principle of publicity like requirement to formation of democratic systems and strengthening of public sphere. The need of publicity of public think refer itself to governamental transparency and opacitys notions, terms that have not yet consolidated itself, but have stimulated discussion that may be a lot enriched to Informtion Science. The interviews made in this case have proved that the notions of transparency and opacity relationed on a set of complementary because they both present themselfs into gradual plan, like reflex of dispute between the visible power and invisible power. The interviewed identify both this notion in to proccess of budget execution. The result release that techinical and politicians directions obstruct the full use of potential of transparency that Siafi may offer to budget execution.